Semiconductor physics and devices - Neamen, D. A.; Neamen, D. A. (New Delhi, Tata McGraw Hill, 2003)
The book provides the basics for the study of electrical properties and characteristics of semiconductor materials and devices . The goal of the book is to bring together the Quantum Mechanics, the Quantum theory of solids , Semiconductor material physics, and semiconductor device physics in a clear and understandable way. Key Features: 934 problems given in the book (solved/unsolved/objective type). Extensive coverage of physics and quantum theory in chapters 2 and 3 prepare the student for a deeper understanding. Comprehensive coverage of the semiconductor devices is presented from chapter 7 onwards. Each chapter treats a different device family. Design examples and homework problems help students.
Appendix A-D 681-690p.; Index 691-705p.
Keywords: Devices; Semicounductors physics; Physics